Hypolipidemic Effects of Modified Edamame Tempeh Flour on Lipid Profile Levels in Dyslipidemia Rats - Dika Nurkistin; Didik Gunawan Tamtomo; Budiyanti Wiboworini (Amerta Nutrition, 2022)
Background: Dyslipidemia is a lipid metabolism disorder that causes an increase or decrease in plasma lipid concentrations. Comprehensive management is an attempt to prevent and reduce dyslipidemia, one of which is nutritional therapy. Edamame contains nutrients such as protein, fat, fiber, and isoflavones that have the potential to improve lipid profiles. Edamame tempeh production is one way to improve product quality that is improving nutritional quality, digestibility, and bioavailability. Edamame tempeh modification is conducted by adding yeast Saccharomyces cerevisiae. This yeast plays a role in increasing the isoflavone levels and the product containing β-glucan.